WANITA DAN EKPOLITASI KAPITALISME - Saiman Saiman (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2010)
This writing aim to find woman exploitated and capitalism phenomenon, that represented by multy national cooperation (MNC). The result shown, capitalism make strong influence to the young womans work at several shops (MNS's). Average of age 16 till 27 years old. There is no age of school of them. It caused capitalism.